Pencil Lead Electrode Modified with Gold Thin Layer for Voltammetric Detection of Chromium (VI) - Sari, Trisna Kumala; Riga, Riga; Zubir, Moondra (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
Cr(VI) is a toxic, mutagenic, and carcinogenic metal. This heavy metal have effect harmful on organism and the environment. In this study, an electroanalytic approach was improved for detection of the Cr(VI) using a pencil lead electrode modified with gold thin layer by cyclic voltammetry. Gold thin layer was electrodeposited on the pencil lead electrode surface with potential-sweeping technique at scan of potential from 1.2 V to 0 V. Since the Cr(VI) species depends on the pH, effect of supporting electrolytes matrix at various pH were investigated. It was found that Cr(VI) gave a reduction peak with a peak potential of 0.35 V vs Ag/AgCl in cyclic voltammogram with 0.1M HClO4 as supporting electrolyte. The calibration curve for Cr(VI) at gold thin layer modified pencil lead electrode shows linearity in range of 5 µM to 100 µM with a detection limit of 2.3 µM achieved.